Characteristics of dust pollution and its influencing factors during cold period of open-pit coal mines in northern China - Wang, Heng; Wang, Zhiming; Wang, Ruixin (Frontiers in Earth Science, 2025)
IntroductionWinter dust pollution in China’s northern open-pit coal mines is serious, and the prevention and control of winter dust pollution is one of the important problems in the construction of green mines in northern open-pit coal mines.MethodsIn this study, we collected dust concentration data, meteorological data, and production data from the experimental mine from 1 December 2018, to 28 February 2019. The characteristics of changes in meteorological factors, production intensity and dust concentration in open-pit coal mines during the cold period are introduced, and the correlation between these factors and dust concentration was analyzed using multivariate statistical analysis methods, dust concentration estimation model including near-surface meteorological factors, high-altitude meteorological factors, and production intensity was developed.ResultsThe results show that the temperature inside the pit is lower the humidity is higher and the wind speed is smaller than outside the pit in winter; there is a long time inversion phenomenon inside the quarry, and there is less vertical convection in the atmosphere (between 8 a.m. and 12 a.m.). Humidity, noise and particulate mass concentration were significantly positively correlated (the lowest correlation coefficient is 0.480 and 0.369 for humidity and noise); wind speed, solar radiation and boundary layer height were significantly negatively correlated with particulate mass concentration (the lowest correlation coefficient is −0.555, −0.280 and −0.510 for wind speed, solar radiation and boundary layer height). The relative frequency of small particulate dust mass concentrations exceeding the national ambient air quality standard limits is greater in winter, and there is a good correlation between the mass concentrations of Total Suspended Particulates (TSP), Particulate Matter 10 (PM10) and Particulate Matter 2.5 (PM2.5). The accuracy of the particulate matter concentration estimation model constructed by considering the influence of multiple factors was significantly higher (R2 for each model rose by nearly 0.3) than that of the model constructed by considering only the near-surface meteorological factors.DiscussionThe research results can provide a reference for the establishment of a more accurate dust estimation model to help the mining sector to better dust prevention and control.